EFSUMB Guidelines 2011: Comment on Emergent Indications and Visions - Dietrich, C. F.; Cui, X. W.; Barreiros, A. P.; Hocke, M.; Ignee, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
The focus of this article is the emergent and potential indications of contrast-enhanced ultrasound (CEUS). Emergent applications of CEUS techniques include extravascular and intracavitary contrast-enhanced ultrasound, quantitative assessment of microvascular circulation for tumor response assessment, and tumor characterization using dynamic contrast-enhanced ultrasound (DCE-US). Potential indications for microbubble agents include novel molecular imaging and drug and gene delivery techniques, which have been successfully tested in animal models. “Comments and Illustrations of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) Non-Liver Guidelines 2011” which focus more on established applications are published in the same supplement to Ultraschall in der Medizin (European Journal of Ultrasound).
Keywords: diagnosis; characterisation; metastases; hepatocellular carcinoma; guidelines; hemangioma; microbubble contrast agent